Deletion of LRP5 and LRP6 in dendritic cells enhances antitumor immunity. (2nd April 2016) - Hong, Yuan; Manoharan, Indumathi; Suryawanshi, Amol; Shanmugam, Arulkumaran; Swafford, Daniel; Ahmad, Shamim; Chinnadurai, Raghavan; Manicassamy, Balaji; He, Yukai; Mellor, Andrew L.; Thangaraju, Muthusamy; Munn, David H.; et al.
ABSTRACT: The tumor microenvironment (TME) contains high levels of the Wnt family of ligands, and aberrant Wnt-signaling occurs in many tumors. Past studies have been directed toward how the Wnt signaling cascade regulates cancer development, progression and metastasis. However, its effects on host antitumor immunity remain unknown. In this report, we show that Wnts in the TME condition dendritic cells (DCs) to a regulatory state and suppress host antitumor immunity. DC-specific deletion of Wnt co-receptors low-density lipoprotein receptor-related protein 5 and 6 (LRP5/6) in mice markedly delayed tumor growth and enhanced host antitumor immunity. Mechanistically, loss of LRP5/6-mediated signaling in DCs resulted in enhanced effector T cell differentiation and decreased regulatory T cell differentiation. This was due to increased production of pro-inflammatory cytokines and decreased production of IL-10, TGF-β1 and retinoic acid (RA). Likewise, pharmacological inhibition of the Wnts' interaction with its cognate co-receptors LRP5/6 and Frizzled (Fzd) receptors had similar effects on tumor growth and effector T cell responses. Moreover, blocking Wnt-signaling in DCs resulted in enhanced capture of tumor-associated antigens and efficient cross-priming of CD8 + T cells. Hence, blocking the Wnt pathway represents a potential therapeutic to overcome tumor-mediated immune suppression and augment antitumor immunity.